Colonic mucosa-associated diffusely adherent afaC+ Escherichia coli expressing lpfA and pks are increased in inflammatory bowel disease and colon cancer. Issue 5 (11th July 2013) - Prorok-Hamon, Maelle; Friswell, Melissa K; Alswied, Abdullah; Roberts, Carol L; Song, Fei; Flanagan, Paul K; Knight, Paul; Codling, Caroline; Marchesi, Julian R; Winstanley, Craig; Hall, Neil; Rhodes, Jonathan M; et al.
Abstract : Objective: Colonic mucosa-associated Escherichia coli are increased in Crohn's disease (CD) and colorectal cancer (CRC). They variously haemagglutinate, invade epithelial cell lines, replicate within macrophages, translocate across M (microfold) cells and damage DNA . We investigated genes responsible for these effects and their co-association in colonic mucosal isolates. Design: A fosmid library yielding 968 clones was prepared in E coli EPI300-T1 using DNA from a haemagglutinating CRC isolate, and resulting haemagglutinating clones were 454-pyrosequenced. PCR screening was performed on 281 colonic E coli isolates from inflammatory bowel disease (IBD) (35 patients), CRC (21) and controls (24; sporadic polyps or irritable bowel syndrome). Results: 454-Pyrosequencing of fosmids from the haemagglutinating clones (n=8) identified the afimbrial adhesin afa - 1 operon. Transfection of afa - 1 into E coli K-12 predictably conferred diffuse adherence plus invasion of HEp-2 and I-407 epithelial cells, and upregulation of vascular endothelial growth factor. E coli expressing afaC were common in CRC (14/21, p=0.0009) and CD (9/14, p=0.005) but not ulcerative colitis (UC; 8/21) compared with controls (4/24). E coli expressing both afaC and lpfA (relevant to M-cell translocation) were common in CD (8/14, p=0.0019) and CRC (14/21, p=0.0001), but not UC (6/21) compared with controls (2/24). E coli expressing both afaC and pks (genotoxic) were common in CRC (11/21, p=0.0015) and UC (8/21, p=0.022), but not CD (4/14) compared with controls (2/24). All isolates expressed dsbA and htrA relevant to intra-macrophage replication, and 242/281 expressed fimH encoding type-1 fimbrial adhesin. Conclusions: IBD and CRC commonly have colonic mucosal E coli that express genes that confer properties relevant to pathogenesis including M-cell translocation, angiogenesis and genotoxicity.